Features associated with recurrence beyond 5 years after nephrectomy and nephron-sparing surgery for renal cell carcinoma: development and internal validation of a risk model (PRELANE score) to predict late recurrence based on a large multicenter database (CORONA/SATURN Project) - Brookman‐May, Sabine D.; Pahernik, Sascha; Hohenfellner, Markus (European urology, 2013)
Background - Approximately 10-20% of recurrences in patients treated with nephrectomy for renal cell carcinoma (RCC) develop beyond 5 yr after surgery (late recurrence). - Objective - To determine features associated with late recurrence. - Design, setting, and participants - A total of 5009 patients from a multicenter database comprising 13 107 RCC patients treated surgically had a minimum recurrence-free survival of 60 mo (median follow-up [FU]: 105 mo [range: 78-135]); at last FU, 4699 were disease free (median FU: 103 mo [range: 78-134]), and 310 patients (6.2%) experienced disease recurrence (median FU: 120 mo [range: 93-149]). - Interventions - Patients underwent radical nephrectomy or nephron-sparing surgery. - Outcome measurements and statistical analysis - Multivariable regression analyses identified features associated with late recurrence. Cox regression analyses evaluated the association of features with cancer-specific mortality (CSM). - Results and limitations - Lymphovascular invasion (LVI) (odds ratio [OR]: 3.07; p<0.001), Fuhrman grade 3-4 (OR: 1.60; p=0.001), and pT stage >pT1 (OR: 2.28; p<0.001) were significantly associated with late recurrence. Based on accordant regression coefficients, these parameters were weighted with point values (LVI: 2 points; Fuhrman grade 3-4: 1 point, pT stage >1: 2 points), and a risk score was developed for the prediction of late recurrences. The calculated values (0 points: late recurrence risk 3.1%; 1-3 points: 8.4%; 4-5 points: 22.1%) resulted in a good-, intermediate- and poor-prognosis group (area under the curve value for the model: 70%; 95% confidence interval, 67-73). Multivariable Cox regression analysis showed LVI (HR: 2.75; p<0.001), pT stage (HR: 1.24; p<0.001), Fuhrman grade (HR: 2.40; p<0.001), age (HR: 1.01; p<0.001), and gender (HR: 0.71; p=0.027) to influence CSM significantly. Limitations are based on the multicenter and retrospective study design. - Conclusions - LVI, Fuhrman grade 3/4, and a tumor stage >pT1 are independent predictors of late recurrence after at least 5 yr from surgery in patients with RCC. We developed a risk score that allows for prognostic stratification and individualized aftercare of patients with regard to counseling, follow-up scheduling, and clinical trial design.
Published online ahead of print on June 22, 2012
Gesehen am 08.12.2020